Comparison of vertical jump and sprint performances between 3 × 3 and 5 × 5 elite professional male basketball players - Cabarkapa, D.; Johnson, Q. R.; Aleksic, J.; Cabarkapa, D. V.; Philipp, N. M.; Sekulic, M.; Krsman, D.; Trunic, N.; Fry, A. C. (Frontiers in Sports and Active Living, 2024)
Given its fast-growing popularity and unique on-court competitive demands, 3 × 3 basketball has captured a considerable amount of attention over recent years. However, unlike research focused on studying 5 × 5 basketball players, there is a lack of scientific literature focused on examining countermovement vertical jump (CMJ) and sprint performance characteristics of 3 × 3 athletes. Thus, the purpose of the present study was to compare force-time metrics during both eccentric and concentric phases of the CMJ and acceleration and deceleration capabilities between 3 × 3 and 5 × 5 top-tier professional male basketball athletes. Ten 3 × 3 and eleven 5 × 5 professional basketball players volunteered to participate in the present study. Upon completion of a standardized warm-up, each athlete performed three maximum-effort CMJs, followed by two 10 m sprints. A uni-axial force plate system sampling at 1,000 Hz was used to analyze CMJ force-time metrics and a radar gun sampling at 47 Hz was used to derive sprint acceleration-deceleration measures. Independent t-tests and Hedge's g were used to examine between-group statistically significant differences (p < 0.05) and effect size magnitudes. The findings of the present study reveal that 3 × 3 and 5 × 5 professional male basketball players tend to display similar neuromuscular performance characteristics as no significant differences were observed in any force-time metric during both eccentric and concentric phases of the CMJ (g = 0.061-0.468). Yet, prominent differences were found in multiple measures of sprint performance, with large effect size magnitudes (g = 1.221-1.881). Specifically, 5 × 5 basketball players displayed greater average and maximal deceleration and faster time-to-stop than their 3 × 3 counterparts. Overall, these findings provide reference values that sports practitioners can use when assessing athletes' CMJ and sprint performance capabilities as well as when developing sport-specific training regimens to mimic on-court competitive demands.